Legal Pluralism as Pancasila’s Reflection to Realize Substantive Justice in Law Enforcement and Law-Making - Samuel Hamonangan Simanjuntak; FX. Djoko Priyono (Badan Pembinaan Ideologi Pancasila, 2022)
The legislation and law enforcement has a causal relationship, if the law does not reflect substantive justice, then law enforcement does not produce substantive justice. There are still many laws that do not reflect substantive justice and law enforcement does not produce substantive justice and does not reflect Pancasila, due to an inappropriate approach. Then what is the fixed approach if you want the law to reflect substantive justice and Pancasila, as well as what is the right approach so that law enforcement produces substantive justice. Based on the above, the problems raised are: whether the legal pluralism approach can realize substantive justice; and how is the legal pluralism approach as a reflection of Pancasila in realizing substantive justice for the formation of laws and law enforcement. The purpose of this study is to formulate that the legal pluralism approach can realize substantive justice and to construct the idea of ​​a legal pluralism approach as a reflection of Pancasila in realizing substantive justice for the formation of laws and law enforcement. The results of this study are that based on the development and concept of the legal pluralism approach, it is a combination of 3 approaches (natural law, state positivism, socio-legal) which will lead to the achievement of substantive justice. To produce laws that reflect substantive justice and Pancasila and law enforcement that produces substantive justice, legislators and law enforcement must use the right approach, namely the legal pluralism approach.